Masturbation parameters related to orgasm satisfaction in sexual relationships: Differences between men and women - Cervilla, Oscar; Sierra, Juan Carlos (Frontiers in Psychiatry, 2022)
Objective: Masturbation is a behavior that can enhance sexual functioning. This study aims to analyze differences between men and women in different masturbation parameters, and to examine their relation with orgasm satisfaction in sexual relationships. Method: 1,335 men and women from the Spanish population aged 18-83 years (M = 36.91; SD = 11.86) participated in an online survey. A questionnaire was used to collect socio-demographic. Sexual history data, negative attitude toward masturbation, solitary sexual desire and orgasm subjective experience upon masturbation were assessed. Given the differences between men and women, independent regression models are proposed to explain orgasm satisfaction in the sexual relationships context. Findings: Men, compared to women, masturbated at a younger age (p < 0.001), and reported higher current masturbation frequency (p < 0.001) and more solitary sexual desire (p < 0.001). Women reported greater intensity in the subjective orgasm experience on its Affective (p < 0.001), Sensory (p < 0.001) and Intimacy (p < 0.001) dimensions. Regarding regression models, the Affective dimension of orgasm was a common parameter in men (β = 0.36; p < 0.001) and women (β = 0.24) to explain orgasm satisfaction during sexual relationships. In men, solitary masturbation frequency (β = -0.10; p = 0.027) acquired a significant role. In women, the model also included age (β = 0.09; p = 0.038), negative attitude toward masturbation (β = -0.12; p = 0.005) and solitary sexual desire (β = -0.19; p = 0.001). Conclusion: When dealing with men and women’s orgasm difficulties in the sexual relationships context, it is important to consider the role of masturbation. In men and women, the Affective dimension of the orgasm experience explain the orgasm satisfaction in sexual relationship. Also, in men, the solitary masturbation frequency is negatively related with orgasm satisfaction in sexual relationship, supporting the compensatory hypothesis of masturbation. In women, in addition to the Affective dimension, the orgasm satisfaction in sexual relationship is explained, negatively, by the negative attitude toward masturbation, and positively, by the solitary sexual desire, which could be associated with more sexual self-knowledge. The relevance of masturbation in understanding sexual functioning is highlighted.